2021
DOI: 10.3390/ijms22094459
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Mutations and Genetic Factors Determining NAFLD Risk

Abstract: NAFLD (non-alcoholic fatty liver disease) is a widespread liver disease that is often linked with other life-threatening ailments (metabolic syndrome, insulin resistance, diabetes, cardiovascular disease, atherosclerosis, obesity, and others) and canprogress to more severe forms, such as NASH (non-alcoholic steatohepatitis), cirrhosis, and HCC (hepatocellular carcinoma). In this review, we summarized and analyzed data about single nucleotide polymorphism sites, identified in genes related to NAFLD development … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 228 publications
(186 reference statements)
0
21
0
Order By: Relevance
“…In the Literature, several examples have confirmed the relationship between genetic predisposition and the NAFLD/NASH development. For example, there are studies on family aggregation, on the different prevalence of these conditions based on ethnic groups, and on the higher NAFLD prevalence in some rare genetic syndromes, such as Prader-Willi, lipodystrophy, and abetalipoproteinemia [349,351]. In recent years, genetic studies have looked for differences in gene or protein expression between healthy and NAFLD/NASH individuals to assess whether these differences may later have a significance in influencing the disease expression [348,352].…”
Section: General Premisesmentioning
confidence: 99%
“…In the Literature, several examples have confirmed the relationship between genetic predisposition and the NAFLD/NASH development. For example, there are studies on family aggregation, on the different prevalence of these conditions based on ethnic groups, and on the higher NAFLD prevalence in some rare genetic syndromes, such as Prader-Willi, lipodystrophy, and abetalipoproteinemia [349,351]. In recent years, genetic studies have looked for differences in gene or protein expression between healthy and NAFLD/NASH individuals to assess whether these differences may later have a significance in influencing the disease expression [348,352].…”
Section: General Premisesmentioning
confidence: 99%
“…Overload of FFAs or conditions inducing hyperglycemia produces increased reactive oxygen species (ROS) and reduces mitochondrial biogenesis, prompting mitochondrial dysfunction that, in turn, gives place to both decreased β-oxidation and ATP production, as well as further increased ROS production, in a vicious circle, eventually resulting in IR, central to NAFLD. Genetic factors related (mt-CYB, POLG, HSD17B13) or not (PNPLA3, GCKR, TM6SF2, MBOAT7) to mitochondria could impact this phenomenon [21][22][23][24].…”
Section: Changes In Mitochondrial Functionmentioning
confidence: 99%
“…Recent research helped to establish different mechanisms of the CVD risk in the case of NAFLD sub-types (metabolic and genetic). It is known that carriers of many SNP sites and mitochondrial mutations have a higher susceptibility to NAFLD [17]. However, a protective effect against CAD (coronary artery disease) was shown for several such SNPs [18], suggesting that every mutation site could imply a unique mechanism of NAFLD susceptibility/CVD protection [19].…”
Section: Cardioprotectionmentioning
confidence: 99%
“…In addition, genetic evidence suggests that NAFLD-mediated dyslipidemia is a crucial factor of elevated CVD risk [14]. While many genetic polymorphism sites and mutations are associated with both CVD [15,16] and NAFLD [17], some NAFLD favouring SNPs (single-nucleotide polymorphisms) have been described as decreasing CVD risk [18][19][20]. Other research, however, found no such protection [21,22].…”
Section: Introductionmentioning
confidence: 99%